2002
DOI: 10.1002/bit.10472
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shear stress on expression of a recombinant protein by Chinese hamster ovary cells

Abstract: A flow chamber was used to impart a steady laminar shear stress on a recombinant Chinese hamster ovary (CHO) cell line expressing human growth hormone (hGH). The cells were subjected to shear stress ranging from 0.005 to 0.80 N m(-2). The effect of shear stress on the cell specific glucose uptake, cell specific hGH, and lactate productivity rates were calculated. No morphological changes to the cells were observed over the range of shear stresses examined. When the cells were subjected to 0.10 N m(-2) shear in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 45 publications
2
55
1
Order By: Relevance
“…As the shear protective effect of PF-68 has been reported to be proportional to its concentration (Ma et al, 2004;Zhang et al, 1992), it is important to know if this uptake phenomenon can significantly affect the Pluronic content in the culture medium. For CHO cells, a 0.2% (w/v) PF-68 concentration is commonly used (Keane et al, 2003;Schroder et al, 2004) and we showed that the presence of cells only slightly affects this concentration. At 0.2% (w/v) with 4 Â 10 6 cells/mL, only a 2.4% decrease of the initial concentration was observed, after 18 h. At the end of a classical bioreactor culture, cell densities can reach up to 10 Â 10 6 cells.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As the shear protective effect of PF-68 has been reported to be proportional to its concentration (Ma et al, 2004;Zhang et al, 1992), it is important to know if this uptake phenomenon can significantly affect the Pluronic content in the culture medium. For CHO cells, a 0.2% (w/v) PF-68 concentration is commonly used (Keane et al, 2003;Schroder et al, 2004) and we showed that the presence of cells only slightly affects this concentration. At 0.2% (w/v) with 4 Â 10 6 cells/mL, only a 2.4% decrease of the initial concentration was observed, after 18 h. At the end of a classical bioreactor culture, cell densities can reach up to 10 Â 10 6 cells.…”
Section: Discussionmentioning
confidence: 92%
“…Each Pluronic fits for a specific application, from drug solubilization to bioprocess applications. For instance, Pluronic F-68 (PF-68, (EO) 75 -(PO) 30 -(EO) 75 ) is used as a shear protective agent which limits cell death in mechanically agitated gas-sparged bioreactors (Murhammer and Goochee, 1990) and is particularly useful in serum-free medium culture (Keane et al, 2003;Schroder et al, 2004). The protective effect of PF-68 has been demonstrated for suspension culture of mammalian cells (Jordan et al, 1994;Ramirez and Mutharasan, 1990;Zhang et al, 1992), insect cells (Goldblum et al, 1990;Murhammer and Goochee, 1990), and plant cells (Sowana et al, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…However, Sf9 perfusion cultures up to 30 Â 10 6 cells ml À1 with a viability maintained at $90% have been reported despite using the ultrasonic separator in the recirculation mode (Zhang et al 1998). The cultivation medium used in that study contained 1% serum (FBS), which can be an effective protecting agent against hydrodynamic stress (McQueen and Bailey 1989;Kunas and Papoutsakis 1990;Chisti 2001;Ma et al 2002;Keane et al 2003). In Figure 4, serum free medium was used, which could explain the greater sensitivity of the insect cell culture to shear stress created by recirculation pumping.…”
Section: Production Of Sacbmfx In Perfusionmentioning
confidence: 98%
“…For some cells, shear stress does not affect phenotype; however, other cells have mechanisms to sense and react to shear stress. 32 It was reported that a very low shear stress level (10 neutrophil cell movements. 35 Therefore, it is important to check the shear stress level of the fluid flow while designing a microsystem.…”
Section: Concentration Gradient Of Soluble Biochemicalsmentioning
confidence: 99%